Investigating LGALS3BP/90 K glycoprotein in the cerebrospinal fluid of patients with neurological diseases - Costa, Júlia (Sci Rep, 2020)
Galectin-3 binding protein (LGALS3BP or 90 K) is a secreted glycoprotein found in human body fluids. Deregulated levels were observed in cancer and infection and its study in neurological diseases is more recent. Here, we have investigated 90 K from human cerebrospinal fluid (CSF) of patients with amyotrophic lateral sclerosis (ALS, n = 35) and other neurological diseases (n = 23). CSF was fractionated by ultrafiltration/size-exclusion chromatography (SEC) and eluted fractions were analysed by complementary techniques including immunoblotting, electron microscopy and nano-liquid chromatography-tandem mass spectrometry. A fraction of 90 K appeared as nanoparticles of irregular shape with heterogeneous dimensions of 15–60 nm that co-eluted with extracellular vesicles in SEC. Median levels of 90 K quantified by ELISA were not different between ALS patients (215.8 ng/ml) and controls (213.3 ng/ml) in contrast with the benchmark biomarker for ALS phosphoneurofilament heavy chain (1750 and 345 pg/ml, respectively). A multiregression model supported age is the only independent predictor of 90 K level in both groups (p < 0.05). Significant correlation was found between 90 K levels and age for the ALS group (r = 0.366, p = 0.031) and for all subjects (r = 0.392, p = 0.003). In conclusion, this study unveils the presence of 90 K-containing nanoparticles in human CSF and opens novel perspectives to further investigate 90 K as potential aging marker.